Annulus and Disk Complex Is Contractible and Quasi-Convex (Communications in Mathematical Research, 2021)
The annulus and disk complex is defined and researched. Especially, weprove that this complex is contractible and quasi-convex in the curve complex.
Keywords: annulus and disk complex; contractible; quasi-convex.